2018
DOI: 10.1093/pm/pny176
|View full text |Cite
|
Sign up to set email alerts
|

Restored Self: A Phenomenological Study of Pain Relief by Cannabis

Abstract: We propose the term Restored Self to conceptualize the effect of medical cannabis. Restored Self is the experience of regaining one's sense of self, sense of normality, and sense of control over one's life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 14 publications
2
18
0
Order By: Relevance
“…In the remaining studies, nine included exclusively "self-identi ed MC users", i.e. those patients who are using MC without the advice of a physician or without an MD con rmed diagnosis [34,73,74,77,81,84,91,94,98,99], four included both self-identi ed and quali ed MC users [51,65,79,93], seven included patients who were seeking MC certi cation or recerti cation [52,53,59,64,67,68,71,96], and eight did not provide su cient details to discriminate between the two categories [36,62,66,69,70,80,88,100].…”
Section: Participants' Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the remaining studies, nine included exclusively "self-identi ed MC users", i.e. those patients who are using MC without the advice of a physician or without an MD con rmed diagnosis [34,73,74,77,81,84,91,94,98,99], four included both self-identi ed and quali ed MC users [51,65,79,93], seven included patients who were seeking MC certi cation or recerti cation [52,53,59,64,67,68,71,96], and eight did not provide su cient details to discriminate between the two categories [36,62,66,69,70,80,88,100].…”
Section: Participants' Characteristicsmentioning
confidence: 99%
“…Of the 20 studies that examined the impact of MC use on the utilization of other prescribed medications [18,34,58 Table 2). In twelve studies, it had been observed that participants discontinued their use of opioids or other prescription drugs following the start of MC consumption [34,58,64,66,68,71,72,75,[95][96][97][98][99], in a proportion varying from 6% [71] to 63% of participants [75]. Participants also reported preferring the use of MC to prescription medication [61], mainly because of the adverse effects of their prescription drugs [76].…”
Section: Medical Cannabis Used As a Substitute For Prescription Medicmentioning
confidence: 99%
“…Data were obtained using different approaches. Nine studies were qualitative and data were collected by interview [56,58,63,74,77,84,91,93,96]. Three studies used closed-ended questions with free space for comments or open-ended questions [60,65,98].…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
“…Participants had been recruited at different locations, with MC or cannabis dispensaries, MC associations or MC advocacy groups as the most frequent recruitment sites (reported in 20 out of the 49 included studies) [18, 54-58, 60-62, 65, 66, 70, 73, 75, 78, 81, 87, 88, 92, 97-99]. Other reported recruitment sites were MC clinics [52,53,59,71], pain or health-care clinics [36,63,64,68,69,72,76,79,80,82,86,95,96], pharmacies specialized in MC distribution [83,89], other pharmacies [85,93], newspapers, university websites, mass media, restaurants or bookstores [34,77,84,99], social media or social networks [84,91,98,99], online forum or websites of MC association [51, 74,94], a Public Health Agency [89,90] and industry-based consumers directed organizations or consumers/patients' organizations [67,91].…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation